2019
DOI: 10.1111/iar.12296
|View full text |Cite
|
Sign up to set email alerts
|

A visage of early Paleozoic Japan: Geotectonic and paleobiogeographical significance of Greater South China

Abstract: The current state of knowledge on the early Paleozoic evolution of Japan is reviewed. Although early Paleozoic Japan marked the foundation of long‐lasting subduction‐related orogenic growth throughout the Phanerozoic, details of this have not been fully revealed. Nevertheless, U‐Pb dating of zircons both in Paleozoic granitoids and sandstones is revealing several new aspects of early Paleozoic Japan. The timing of the major tectonic change, from a passive continental margin setting (Stage I) to an active one (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 108 publications
2
32
0
Order By: Relevance
“…These new fossil data have enabled integration of the Japanese rock succession into existing high‐resolution Silurian chitinozoan and conodont biozonation schemes, including correlation with the type Silurian of the Welsh Borderland in the UK (Vandenbroucke et al, ). Furthermore, a more precise understanding of the paleogeographical context of proto‐Japan as an evolving arc situated close to Greater South China during the early Paleozoic (Isozaki, ), supports the contention of several papers presented here that paleoenvironment, paleoecology and paleoclimate exert strong controls on the paleobiogeographical signatures of the faunas and that these factors need to be considered in assessments of paleogeographical affinity. Thus, the faunas of the SKT, HGT, and KT show affinities, sometimes at the species‐level, with fossil assemblages of the North China paleocontinent, the South China paleocontinent, and the Australian segment of East Gondwana, though limestone and siliciclastic lithofacies display contrasting signatures (cf.…”
supporting
confidence: 84%
“…These new fossil data have enabled integration of the Japanese rock succession into existing high‐resolution Silurian chitinozoan and conodont biozonation schemes, including correlation with the type Silurian of the Welsh Borderland in the UK (Vandenbroucke et al, ). Furthermore, a more precise understanding of the paleogeographical context of proto‐Japan as an evolving arc situated close to Greater South China during the early Paleozoic (Isozaki, ), supports the contention of several papers presented here that paleoenvironment, paleoecology and paleoclimate exert strong controls on the paleobiogeographical signatures of the faunas and that these factors need to be considered in assessments of paleogeographical affinity. Thus, the faunas of the SKT, HGT, and KT show affinities, sometimes at the species‐level, with fossil assemblages of the North China paleocontinent, the South China paleocontinent, and the Australian segment of East Gondwana, though limestone and siliciclastic lithofacies display contrasting signatures (cf.…”
supporting
confidence: 84%
“…4 B).
Figure 4 ( a ) The overall framework of the adjacent, major continental blocks and schematic profile across the OT and the China Block; modified from Isozaki 45 . The five-pointed stars show the sampling locations for this study, Li et al 31 and Yuan et al 30 .
…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the origin and affinity of the Khanka Block, Isozaki et al (2017) suggested that the Khanka Block (as well as the Sergeevka blocks/nappes in the Russian Far East) may be the northern extension of SW Japan that originally formed of Greater South China. The major evidence is that the Neoproterozoic zircon ages from the Late Paleozoic strata in the Primorye, Russian Far East are very similar to those from the older components in SW Japan, which were typical of the South China Block (Isozaki, 2019;Isozaki et al, 2017). On the other hand, Zhou et al (2010Zhou et al ( , 2018 linked the Jiamusi-Khanka Block to the southern margin of the Siberia Craton according to similar rock assemblages of Neoproterozoic/early Phanerozoic age.…”
Section: Geological Backgroundmentioning
confidence: 92%
“…Liu, Zhang, Wilde, Zhou, et al, 2017;Zhou & Li, 2017;Zhou et al, 2009Zhou et al, , 2014. However, the early subduction history was dated to the early Permian (Sun, Xu, Wilde, Chen, & Yang, 2015), or even the Cambrian as evidenced by arc-like granitoids and blueschists in SW Japan (Isozaki, 2019;Isozaki et al, 2015). 3a was drawn using software GMT 6.0 and Figure 3b is modified after Khanchuk et al (2016).…”
Section: Geological Backgroundmentioning
confidence: 99%